The extent and determinants of vegetable commercialization among smallholders in Sebeta Hawas Woreda, Oromia Region, Ethiopia - Asfaw Shaka Gosa; Tebarek Lika Megento; Meskerem Abi Teka (Cogent Social Sciences, 2024)
This study aimed to investigate the extent and determinants of vegetable commercialization among smallholders in the Sebeta Hawas Woreda, Oromia region, Ethiopia. Data were collected through surveys of 385 farm households. The study results indicated that vegetable production in the study area is highly commercialized in terms of vegetable output marketed with an average commercialization extent of 74.2% although vegetable commercialization extent is at a low level (34.82%) in terms of land areas allotted to vegetable production. The results of the truncated Tobit regression model revealed that the extent of vegetable commercialization was significantly and positively influenced by the gender of the household head, year of schooling, family size, access to irrigation facilities, cooperative membership, access to credit services, contact with extension agents, access to improved seeds, access to chemical fertilizers, and access to market information. Conversely, the age of the household head, livestock holdings, and participation in off-farm activities significantly and negatively influenced the extent of vegetable commercialization. The study suggests that vegetable commercialization can be enhanced by supplying farm inputs such as improved seeds, chemical fertilizers, pesticides, and irrigation equipment. In addition, designing gender-focused intervention programs is essential to promote the equal participation of both men and women in vegetable production and marketing. Moreover, providing adequate and relevant market information and strengthening farmers’ cooperatives can enable smallholder farmers to access the market and increase their market participation so that they can obtain reasonable returns from the vegetable business.